FROM FORMAL CLASS TO COMMUNITY: AN EXPERIMENT IN THE TEACHING OF FRENCH PROSE COMPOSITION - Pascal, Gabrielle (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1974)
French composition courses, part of the honors and major programs in French at McGill, have an essential but somewhat unappreciated role to play in the education of undergraduate students. Their aim is to determine, and then increase, the students' ability in written French so as to enable them to master the range of expression and thus, to broaden and deepen their comprehension of literary texts. The difficulties which lie in wait for both students and instructors demand an exploration of the conditions necessary for creating a sympathetic state of mind, a viable program and an appropriate pedagogical method for this kind of course.